2021
DOI: 10.1097/cce.0000000000000434
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II for Near Drowning: A Case Series

Abstract: Objective: This case series describes the effect of angiotensin II administration on hemodynamics in patients with parenchymal lung injury due to submersion injury. Case Summary: A 33-year-old female and a 72-year-old female were both brought to the emergency department after incidents of near drowning. Upon arrival to the emergency department, both patients were hemodynamically unstable and were eventually intubated for airway protection. Imaging done by conventional chest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Additional case studies or case series performed outside the clinical trial setting also reported ATII response in distributive shock associated with cirrhosis, postcardiopulmonary bypass, liver transplant, near drowning, and COVID-19, providing further limited evidence for ATII efficacy (31–36).…”
Section: Discussionmentioning
confidence: 99%
“…Additional case studies or case series performed outside the clinical trial setting also reported ATII response in distributive shock associated with cirrhosis, postcardiopulmonary bypass, liver transplant, near drowning, and COVID-19, providing further limited evidence for ATII efficacy (31–36).…”
Section: Discussionmentioning
confidence: 99%